A comparative study of test methods for assessment of fire safety performance of bus interior materials. (2nd October 2011) - Försth, Michael; Modin, Håkan; Sundström, Björn
SUMMARY: This work concerns the assessment of fire performance of interior materials in buses. The widely used test method ISO 3795/FMVSS 302 has received much criticism mainly based on the fact that the test is a small‐scale method not suited for bus fires induced by for example fire in the engine compartment or fire in a tyre. Furthermore, test specimens are oriented horizontally, whereas much fire spread in a real bus fire occurs on vertically oriented products. Seventeen products were investigated: 11 textiles, four solids and two insulations. Three test methods were compared: ISO 3795, ISO 6941 and ISO 5658‐2. Given the existing criteria for interior materials, it was found that ISO 6941 and ISO 5658‐2 place harder requirements on the materials. When the three methods were compared, it was found that ISO 3795/FMVSS 302 and ISO 6941 are insufficient for simulating bus fires typically occurring today. Such fires are often initiated by a fire in the engine compartment or in a tyre and can hardly be simulated by small‐scale methods as ISO 3795/FMVSS 302 or ISO 6941 even if the ISO 6941 method to some extent gives results similar to the established large‐scale ISO 5658‐2 method. Copyright © 2011 John Wiley & Sons, Ltd.